Benzo-extended cyclohepta[def]fluorene derivatives with very low-lying triplet states - Wu, F; Ma, J; Lombardi, F; Fu, Y; Liu, F; Huang, Z; Liu, R; Komber, H; Alexandropoulos, DI; Dmitrieva, E; Lohr, TG; Israel, N; et al. (Wiley, 2022)
Open-shell non-alternant polycyclic hydrocarbons (PHs) are attracting increasing attention due to their promising applications in organic spintronics and quantum computing. Herein we report the synthesis of three cyclohepta[def]fluorene-based diradicaloids ( 1-3 ), by fusion of benzo rings on its periphery for the thermodynamic stabilization, as evidenced by multiple characterization techniques. Remarkably, all of them display a very narrow optical energy gap ( E g opt = 0.52-0.69 eV) and persistent stability under ambient conditions ( t 1/2 = 11.7-33.3 h). More importantly, this new type of diradicaloids possess a low-lying triplet state with an extremely small singlet-triplet energy gap, as low as 0.002 kcal/mol, with a clear dependence on the molecular size. This family of compounds thus offers a new route to create non-alternant open-shell PHs with high-spin ground states, and opens up novel possibilities and insights into understanding the structure-property relationships.